Real options approach for technology renewal in an Electronic Manufacturing Service (EMS) company - Zarate Carbajal, Jose Mario; Ruiz-Cruz, Riemann; Sanchez-Torres, Juan Diego (International Journal of Applied Research in Management and Economics, 2022)
Electronic Manufacturing Services (EMS.) companies are in a highly competitive environment where investment in technology plays a significant role in the company's performance. The equipment efficiency is directly converted to revenue. The equipment efficiency decays over time; keeping the equipment represents a loss in productivity, and renewing the equipment requires an additional cost. There is a continuous decision process to determine the optimal time to replace the old equipment with a new one. Traditionally, the optimal time to renew is when the machine's revenue matches the cost. This paper studies the renewal decision using a real options approach, adding the uncertainty factor. The variables are modeled as Geometric Brownian Motions. We provide a literature review of renewal real options and describe the models we use. The one-factor model considers the revenue as stochastic; the two-factor model considers the revenue and cost as stochastic; the technological improvement models extend the two-factor model to include a premium in revenue for replacing the equipment. An overview of the electronic manufacturing dynamics is described; we select a product whose manufacturing process depends on machines. We provide a methodology for the model's implementation and how to determine the parameters; the results are compared to the deterministic approach. Finally, we discuss the models' advantages, disadvantages, and limitations.